ChemInform Abstract: Direct Access to Novel Chromeno—Pyrimidine N‐Oxides via Tandem Base‐Catalyzed Double Nucleophilic Addition/Dehydration Reaction. Issue 25 (3rd June 2013) - Jalli, Venkata Prasad; Jaggavarapu, Satyanarayana Reddy; Kamalakaran, Anand Solomon; Gangisetty, Sravan Kumar; Nanubolu, Jagadeesh Babu; Gaddamanugu, Gopikrishna
Abstract The process is regioselective to give the target compounds (13 examples) in good yields.